2021
DOI: 10.1371/journal.pone.0245268
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of victimisation and mental health prevalence among LGBTQ+ young people with experiences of self-harm and suicide

Abstract: Background LGBTQ+ youth have higher rates of self-harm and suicide than cisgender, heterosexual peers. Less is known about prevalence of risks within these populations. Objectives The first systematic review and meta-analysis to investigate the prevalence of risks among young people throughout the LGBTQ+ umbrella with experiences across the dimension of self-harm, suicidal ideation and suicide behaviour; and how they may differ between LGBTQ+ umbrella groups. Data sources MEDLINE, Scopus, EMBASE, PsycINFO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 137 publications
5
60
0
Order By: Relevance
“…This current study is a pioneer cross-sectional study in France to analyze the role of parental and friend's support on suicide attempts among LGB adolescents. Suicide attempt remained associated with sexual orientation when considering possible related variables, which is consistent with previous studies (Green et al, 2021;Williams et al, 2021). A co-twin control study in youth males showed that suicide attempts remained signi cantly associated with same-gender sexual orientation after adjustment for substance abuse and depressive symptoms (Herrell et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This current study is a pioneer cross-sectional study in France to analyze the role of parental and friend's support on suicide attempts among LGB adolescents. Suicide attempt remained associated with sexual orientation when considering possible related variables, which is consistent with previous studies (Green et al, 2021;Williams et al, 2021). A co-twin control study in youth males showed that suicide attempts remained signi cantly associated with same-gender sexual orientation after adjustment for substance abuse and depressive symptoms (Herrell et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the adolescents associated with sexual minority status show a higher risk of suicide attempts (Greteman, 2015;Teasdale & Bradley-Engen, 2010;Turpin et al, 2020). Adolescents who identify as lesbian, gay, and bisexual (LGB) are at least three times more likely to have attempted suicide than their heterosexual peers (Firdion & Beck, 2015;Seil et al, 2014;Williams et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…LGBTQ2S youth are overrepresented among youth experiencing homelessness and constitute 20–40% of the homeless youth population in North America [ 5 – 9 ]. LGBTQ2S youth experience significantly higher rates of mental health issues compared to heterosexual and cisgender youth across global contexts, due to stigma, discrimination, and identity-based rejection [ 5 , 7 , 10 , 11 ]. Public health measures, such as physical distancing and the closure of social support programs, have undoubtedly resulted in negative outcomes among LGBTQ2S youth at risk of, and experiencing, homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients experienced a statistically significant (p-value = 5.4e7 by paired two-sample t-test) average reduction of 0.5 points for question 7 of the PHQ-9 which assesses frequency of suicidal ideation over the past 2 weeks. This finding is especially important given that LGBTQ + people experience disproportionately high rates of suicidality (Williams et al, 2021 ). Patients receiving two or more modalities of care experienced on average a 37% reduction in PHQ-9 scores and a 56% reduction in GAD-7 scores after 12 weeks, compared to a 17% reduction in PHQ-9 scores and 11% reduction in GAD-7 scores in patients who received only one modality of care (Fig.…”
Section: Resultsmentioning
confidence: 99%